1984
DOI: 10.1159/000172937
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalciuric Effects of Hydrochlorothiazide in the Rat during NaHCO<sub>3</sub>, NaCl and NH<sub>4</sub>C1 Loading

Abstract: Hydrochlorothiazide (HCTZ) and NaHCO3 each lower urinary calcium excretion, while NaCl and NH4Cl each increase urinary calcium. This study examines the ability of HCTZ to lower urinary calcium during NaHCO3, NaCl and NH4Cl loading in the rat. We show that HCTZ lowers urinary calcium in rats treated with NaHCO3, NaCl and NH4Cl. We demonstrate that urinary calcium excretion is depressed to a greater degree by administering NaHCO3 and HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…There are no comparable results in the literature from trials with human subjects on the combined effect of increased Na and protein intake on urinary Ca excretion in adults. There is some evidence from animal studies that the calciuric effects of high Na and high protein intakes may be additive (Goulding & Campbell, 1984;Chan & Swaminathan, 1994). To place the Na and/or protein-induced calciuria observed in the present study in the context of bone health, it has been estimated that a net deficit of only 1 mmol Ca/d would result in losing one-third of the Ca contained in the typical adult skeleton in just over 20 years, unless a compensatory increase in the efficiency of intestinal Ca absorption and/ or decrease in endogenous loss of Ca occurred (Shortt & Flynn, 1990;Sellmeyer et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no comparable results in the literature from trials with human subjects on the combined effect of increased Na and protein intake on urinary Ca excretion in adults. There is some evidence from animal studies that the calciuric effects of high Na and high protein intakes may be additive (Goulding & Campbell, 1984;Chan & Swaminathan, 1994). To place the Na and/or protein-induced calciuria observed in the present study in the context of bone health, it has been estimated that a net deficit of only 1 mmol Ca/d would result in losing one-third of the Ca contained in the typical adult skeleton in just over 20 years, unless a compensatory increase in the efficiency of intestinal Ca absorption and/ or decrease in endogenous loss of Ca occurred (Shortt & Flynn, 1990;Sellmeyer et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that a doubling of dietary protein intake increases daily urinary Ca excretion by approximately 50 % (Walker & Linkswiler, 1972;Heaney, 1993). Furthermore, there is some evidence from animal studies that the calciuric effects of high Na and high protein intakes may be additive (Goulding & Campbell, 1984;Chan & Swaminathan, 1994). However, it is not known to what extent Na-(and/or protein-) induced calciuria is compensated for by increased absorption of dietary Ca and/or reduced endogenous Ca losses or to what extent this urinary Ca is derived from resorption of bone (Shortt & Flynn, 1990;Itoh et al 1998).…”
mentioning
confidence: 99%
“…Composition of perfusion fluids is given in Table I. To identify proximal tubules having four or more surface segments, a solution containing 0.5 g/liter Brilliant Blue FCF dye (Pfaltz & Bauer, Inc., Stamford, CT) was injected into a tubule segment by means of a micropipette (3)(4)(5) Am o.d.) and was observed as it flowed downstream.…”
Section: Methodsmentioning
confidence: 99%
“…Bicarbonate administration is known to decrease urinary calcium excretion in acidotic (1)(2)(3) and nonacidotic states (4). Sutton et al (2) showed that infusion of HCO3 to dogs did not enhance proximal Ca reabsorption and concluded that the decreased urinary Ca excretion was the result ofa direct HCO3 effect to increase Ca absorption beyond the late proximal tubule.…”
Section: Introductionmentioning
confidence: 99%